THE ROLE AND INFLUENCE OF THE LEADERSHIP OF TERRITORIAL COMMUNITIES IN THE WAR PERIOD: CHALLENGES AND PROSPECTS - RUDACHENKO, Olha; UGODNIKOVA, Оlena; TROIAN, Vladyslava (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The study demonstrated the importance of local self-government in conditions of war on the territory of Ukraine, both for the inhabitants of the community and the country in general, focusing on the maintenance and restoration of infrastructure, housing, utilities and cultural and historical heritage. The active role of local self-government bodies in the implementation of necessary changes and strengthening of institutions was emphasized. Highlighting the leading position of local authorities in making important decisions for the effective functioning of territorial communities is a key aspect of the study, especially in view of the future prerequisites for post-war reconstruction. Challenges and future prospects faced by territorial communities during the war period are listed, such as: collecting funds for the needs of the army, providing volunteer assistance in the form of food products, medical equipment and personal protection for fighters, as well as attracting resources and expertise for the implementation of projects to support the military and their families, etc. In addition, territorial communities are aimed at raising awareness and moral and psychological support of military personnel, as well as attracting citizens to participate in the defense of the country through participation in volunteer activities and other forms of local defense. The budgets of territorial communities of the Kharkiv region were analysed and the financial resources that were provided in the form of assistance to the Ukrainian army were identified. It is proven that despite the fact that the Kharkiv region directly borders with the aggressor country – Russia, as well as in some communities of Kharkov, active fighting is being carried out, the city still remains in the leading positions among internally displaced persons and the business that relocated to this city. The study also provides basic recommendations that will help territorial communities to demonstrate their leadership positions in the war and post-war periods. These include: strategic leadership, organizational skills, psychological support, international relations, adaptation and response.
Keywords: territorial community; leadership; development; entrepreneurship; financial resources